2023
DOI: 10.1186/s12888-023-05199-5
|View full text |Cite
|
Sign up to set email alerts
|

Blood miRNA levels associated with ADHD traits in children across six European birth cohorts

Lene B. Dypås,
Nur Duale,
Ann-Karin Olsen
et al.

Abstract: Background Attention-deficit/hyperactivity disorder (ADHD) is a prevalent and highly heritable neurodevelopmental disorder of major societal concern. Diagnosis can be challenging and there are large knowledge gaps regarding its etiology, though studies suggest an interplay of genetic and environmental factors involving epigenetic mechanisms. MicroRNAs (miRNAs) show promise as biomarkers of human pathology and novel therapies, and here we aimed to identify blood miRNAs associated with traits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Srivastav et al ( 69 ) observed that peripheral microRNA concentrations were different in both animal models and children with ADHD. In 2023, Dypås et al discovered 32 microRNAs that were strongly linked to features related to ADHD, including hyperactivity (29) and inattention (3) ( 70 ).…”
Section: The Etiology and Pathogenesis Of Adhdmentioning
confidence: 99%
“…Srivastav et al ( 69 ) observed that peripheral microRNA concentrations were different in both animal models and children with ADHD. In 2023, Dypås et al discovered 32 microRNAs that were strongly linked to features related to ADHD, including hyperactivity (29) and inattention (3) ( 70 ).…”
Section: The Etiology and Pathogenesis Of Adhdmentioning
confidence: 99%
“…The prevalence of attention deficit hyperactivity (ADHD) in worldwide population is estimated to be 5.9% among youths and 2.5% among adults (Faraone et al 2021 ). Diagnosis of ADHD is challenging due to missing gaps related to knowledge of its etiology (Dypås et al 2024 ). Individuals with ADHD were reported to have differences in their brain processes, which produce changes in personal, social, academic, and occupational functioning (American Psychiatric Association 2022 ).…”
Section: Introductionmentioning
confidence: 99%